A study on english teachers’ perceptions towards the use of augmented reality (AR) in secondary school ESL classroom / Mohd Sufi Amin Salmee. - Salmee, Mohd Sufi Amin (2019)
In meeting the needs of the new generation of learners, the idea of implementing the use of new technology such as Augmented Reality (AR) in English as a Second Language (ESL) classrooms can be a step towards refining the teaching and learning atmosphere. Nevertheless, the use of this technology relies heavily on the teacher’s level of acceptance and skills for it to be successful in classrooms. As the technology is yet to be implemented in the Malaysian Education System, this study can be the early attempt in studying the teachers’ perceptions towards the implementation of this new technology. Thus, the study intended to determine the English language teachers’ perceptions towards the use of AR in secondary school ESL classroom by applying the Technology Acceptance Model (TAM) as the base of the research model. TAM is a theory that was developed based on the adaptation of Theory of Reasoned Action (TRA) and Theory of Planned Behaviour, which consists of four variables that are perceived usefulness (PU), perceived ease of use (PEoU), attitude towards use (ATT) and behavioural intention (BI). A survey was conducted on 180 English teachers from 20 schools in the district of Petaling Perdana. The items in the questionnaire elicited information on the levels of AR acceptance of the respondents based on the four mentioned variables of TAM towards the use AR in ESL classroom. Findings from the study indicate that the levels of AR acceptance of the English teachers are relatively high, as the respondents recorded a high level of PU, ATT and BI towards the use of AR while PEoU was at moderate level. Analysis of the level of AR acceptance based on the respondents’ gender, years of experience in teaching English and academic qualifications revealed that there is a significant influence of English teachers’ years of experienced in teaching English with their BI to use AR while other studied variables were found statistically insignificant in determining the levels of AR acceptance. The result from multiple regression analysis indicate that PU and ATT of the English teachers directly influence their BI to use AR in ESL classroom. The findings reported suggests that English teachers are acceptive and ready for the implementation of AR technology. Nevertheless, in-service trainings on the use of the technology and also awareness on the knowledge of operating the AR devices and software are needed for the teachers to ensure the smooth-running of the use of AR if it were to be implemented in the national curriculum.